Photojournalism-Based Intervention Reduces Caregiver Burden and Depression in Alzheimer's Disease Family Caregivers. (September 2019) - Wharton, Whitney; Epps, Fayron; Kovaleva, Mariya; Bridwell, Lindsey; Tate, Rachanice Candy; Dorbin, Cornelya D.; Hepburn, Kenneth
Purpose: Art interventions have demonstrated holistic benefits for persons living with dementia and their caregivers. In this article, we describe the results of a pilot photojournalism program for 10 unpaid caregivers of persons living with dementia, with respect to caregivers' experience in the program and their psychological well-being.Design: Caregivers participated in four sessions led by a professional photojournalist who taught principles of photography. Between the sessions, caregivers took photographs that represented what caregiving meant to them using digital cameras provided in the program. During the sessions, instruction was interspersed with discussion of caregivers' photographs.Method: Caregiver burden and depressive symptoms were measured pre- and postprogram. Qualitative exploration included sessions' observations, viewing caregivers' photographs, and recording caregivers' accompanying comments.Findings: For participants with pre- and postprogram data, caregiver burden decreased significantly ( p = .037). For caregivers with pre- and postprogram data, depressive symptoms decreased nonsignificantly ( p = .066). Clinically meaningful reductions in caregiver burden and depressive symptoms were attained. Qualitative findings highlighted caregivers' strong engagement with the project, the facilitator, and other participants, and reflection on multiple aspects of their experience.Conclusions: This intervention helped caregivers creatively communicate their experience and demonstrated efficacy in the improvement of caregivers' psychological well-being.